2019
DOI: 10.1101/618124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Amelioration of Mn-induced Chlorosis Facilitated by Mn Down-regulation, Ammonium and Rainwater in Sugarcane Seedlings

Abstract: 2We had previously reported that manganese (Mn)-induced chlorosis is a serious problem 3 in ratoon sugarcane seedlings grown in acidic soils. To further monitor the progression of 4 chlorosis and elucidate the corresponding mechanism, both plant growth and nutrient 5 status of sugarcane plants and soils were investigated in the growth seasons of ratoon 6 cane seedlings in 2016 and 2018. The impacts of rainfall and ammonium on chlorosis 7 were also investigated hydroponically. The results showed that the chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…At the same time, the active Fe de ciency in plantlets played a secondary role [3]. The subsequent investigation revealed that, in the progression of the greening of chlorotic seedling, the leaf Mn content decreased signi cantly, whereas Fe content increased [52]. These results remind us that the metal ion metabolism may exist disorder in chlorosis sugarcane.…”
Section: Discussionmentioning
confidence: 78%
“…At the same time, the active Fe de ciency in plantlets played a secondary role [3]. The subsequent investigation revealed that, in the progression of the greening of chlorotic seedling, the leaf Mn content decreased signi cantly, whereas Fe content increased [52]. These results remind us that the metal ion metabolism may exist disorder in chlorosis sugarcane.…”
Section: Discussionmentioning
confidence: 78%
“…At the same time, the active Fe deficiency in plantlets played a secondary role [3]. The subsequent investigation revealed that, in the progression of the greening of chlorotic seedling, the leaf Mn content decreased significantly, whereas Fe content increased [54]. Mn shares similar chemical properties with Fe and Mn, and Fe interaction was observed in several physiological processes [55].…”
Section: Discussionmentioning
confidence: 97%